Highly sensitive detection of estradiol by a SERS sensor based on TiO2 covered with gold nanoparticles - Brognara, Andrea; Mohamad Ali Nasri, Ili F.; Bricchi, Beatrice R.; Li Bassi, Andrea; Gauchotte-Lindsay, Caroline; Ghidelli, Matteo; Lidgi-Guigui, Nathalie (Beilstein Journal of Nanotechnology, 2020)
We propose the use of gold nanoparticles grown on the surface of nanoporous TiO2 films as surface-enhanced Raman scattering (SERS) sensors for the detection of 17β-estradiol. Gold deposition on top of a TiO2 surface leads to the formation of nanoparticles the plasmonic properties of which fulfil the requirements of a SERS sensor. The morphological and optical properties of the surface were investigated. Specifically, we demonstrate that the TiO2 background pressure during pulsed laser deposition and the annealing conditions offer control over the formation of Au nanoparticles with different sizes, shapes and distributions, yielding a versatile sensor. We have exploited the surface for the detection of 17β-estradiol, an emerging contaminant in environmental waters. We have found a limit of detection of 1 nM with a sensitivity allowing for a dynamic range of five orders of magnitude (up to 100 µM).
Keywords: aptamer; Au nanoparticles; 17-β estradiol (E2); plasmonics; sensor; surface-enhanced Raman scattering (SERS); TiO2 nanostructures

(untitled) - Cottat, M.; D’Andrea, C.; Yasukuni, R.; Malashikhina, N.; Grinyte, R.; Lidgi-Guigui, N.; Fazio, B.; Sutton, A.; Oudar, O.; Charnaux, N.; Pavlov, V.; Toma, A.; et al. (J. Phys. Chem. C, 2015)

(untitled) - Cottat, M.; Lidgi-Guigui, N.; Tijunelyte, I.; Barbillon, G.; Hamouda, F.; Gogol, P.; Aassime, A.; Lourtioz, J.-M.; Bartenlian, B.; de la Chapelle, M. L. (Nanoscale Res. Lett., 2014)

(untitled) - Galarreta, B. C.; Norton, P. R.; Lagugné-Labarthet, F. (Langmuir, 2011)

(untitled) - Tijunelyte, I.; Dupont, N.; Milosevic, I.; Barbey, C.; Rinnert, E.; Lidgi-Guigui, N.; Guenin, E.; de la Chapelle, M. L. (Environ. Sci. Pollut. Res., 2017)

(untitled) - Guillot, N.; Shen, H.; Frémaux, B.; Péron, O.; Rinnert, E.; Toury, T.; Lamy de la Chapelle, M. (Appl. Phys. Lett., 2010)

(untitled) - Moskovits, M. (J. Raman Spectrosc., 2005)

(untitled) - Radziuk, D.; Moehwald, H. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Campion, A.; Kambhampati, P. (Chem. Soc. Rev., 1998)

(untitled) - Jeanmaire, D. L.; Van Duyne, R. P. (J. Electroanal. Chem. Interfacial Electrochem., 1977)

(untitled) - Albrecht, M. G.; Creighton, J. A. (J. Am. Chem. Soc., 1977)

(untitled) - Kneipp, K.; Wang, Y.; Kneipp, H.; Perelman, L. T.; Itzkan, I.; Dasari, R. R.; Feld, M. S. (Phys. Rev. Lett., 1997)

(untitled) - Hulteen, J. C.; Treichel, D. A.; Smith, M. T.; Duval, M. L.; Jensen, T. R.; Van Duyne, R. P. (J. Phys. Chem. B, 1999)

(untitled) - Ben-Jaber, S.; Peveler, W. J.; Quesada-Cabrera, R.; Cortés, E.; Sotelo-Vazquez, C.; Abdul-Karim, N.; Maier, S. A.; Parkin, I. P. (Nat. Commun., 2016)

(untitled) - Alessandri, I.; Lombardi, J. R. (Chem. Rev., 2016)

(untitled) - Li, X.; Chen, G.; Yang, L.; Jin, Z.; Liu, J. (Adv. Funct. Mater., 2010)

(untitled) - Samransuksamer, B.; Horprathum, M.; Jutarosaga, T.; Kopwitthaya, A.; Limwichean, S.; Nuntawong, N.; Chananonnawathorn, C.; Patthanasettakul, V.; Muthitamongkol, P.; Treetong, A.; Klamchuen, A.; Leelapojanaporn, A.; et al. (Sens. Actuators, B, 2018)

(untitled) - Kim, Y. S.; Jung, H. S.; Matsuura, T.; Lee, H. Y.; Kawai, T.; Gu, M. B. (Biosens. Bioelectron., 2007)

(untitled) - Cottat, M.; Lidgi-Guigui, N.; Hamouda, F.; Bartenlian, B.; Venkataraman, D.; Marks, R. S.; Steele, T. W. J.; de la Chapelle, M. L. (J. Opt. (Bristol, U. K.), 2015)

(untitled) - Pavlov, V.; Willner, I.; Dishon, A.; Kotler, M. (Biosens. Bioelectron., 2004)

(untitled) - Song, S.; Wang, L.; Li, J.; Fan, C.; Zhao, J. (TrAC, Trends Anal. Chem., 2008)

(untitled) - Terracciano, M.; Rea, I.; Borbone, N.; Moretta, R.; Oliviero, G.; Piccialli, G.; De Stefano, L. (Molecules, 2019)

(untitled) - Hamid, H.; Eskicioglu, C. (Water Res., 2012)

(untitled) - Liu, S.; Cheng, R.; Chen, Y.; Shi, H.; Zhao, G. (Sens. Actuators, B, 2018)

(untitled) - Wise, A.; O’Brien, K.; Woodruff, T. (Environ. Sci. Technol., 2011)

(untitled) - Vajda, A. M.; Barber, L. B.; Gray, J. L.; Lopez, E. M.; Woodling, J. D.; Norris, D. O. (Environ. Sci. Technol., 2008)

(untitled) - Snyder, S. A.; Keith, T. L.; Verbrugge, D. A.; Snyder, E. M.; Gross, T. S.; Kannan, K.; Giesy, J. P. (Environ. Sci. Technol., 1999)

(untitled) - Long, F.; Zhu, A.; Shi, H. (Sensors, 2013)

(untitled) - Bricchi, B. R.; Ghidelli, M.; Mascaretti, L.; Zapelli, A.; Russo, V.; Casari, C. S.; Terraneo, G.; Alessandri, I.; Ducati, C.; Li Bassi, A. (Mater. Des., 2018)

(untitled) - Di Fonzo, F.; Casari, C. S.; Russo, V.; Brunella, M. F.; Li Bassi, A.; Bottani, C. E. (Nanotechnology, 2009)

(untitled) - Michota, A.; Bukowska, J. (J. Raman Spectrosc., 2003)

(untitled) - Garai-Ibabe, G.; Grinyte, R.; Golub, E. I.; Canaan, A.; de la Chapelle, M. L.; Marks, R. S.; Pavlov, V. (Biosens. Bioelectron., 2011)

(untitled) - Ghidelli, M.; Mascaretti, L.; Bricchi, B. R.; Zapelli, A.; Russo, V.; Casari, C. S.; Li Bassi, A. (Appl. Surf. Sci., 2018)

(untitled) - Doron-Mor, I.; Barkay, Z.; Filip-Granit, N.; Vaskevich, A.; Rubinstein, I. (Chem. Mater., 2004)

(untitled) - Karakouz, T.; Holder, D.; Goomanovsky, M.; Vaskevich, A.; Rubinstein, I. (Chem. Mater., 2009)

(untitled) - Tesler, A. B.; Chuntonov, L.; Karakouz, T.; Bendikov, T. A.; Haran, G.; Vaskevich, A.; Rubinstein, I. (J. Phys. Chem. C, 2011)

(untitled) - Gaspar, D.; Pimentel, A. C.; Mateus, T.; Leitão, J. P.; Soares, J.; Falcão, B. P.; Araújo, A.; Vicente, A.; Filonovich, S. A.; Águas, H.; Martins, R.; Ferreira, I. (Sci. Rep., 2013)

Handbook of Enhanced Spectroscopy - Gucciardi, P. G.; de la Chapelle, M. L.; Lidgi-Guigui, N. (Jenny Stanford Publishing)

(untitled) - Love, J. C.; Estroff, L. A.; Kriebel, J. K.; Nuzzo, R. G.; Whitesides, G. M. (Chem. Rev., 2005)

(untitled) - Félidj, N.; Aubard, J.; Lévi, G.; Krenn, J. R.; Hohenau, A.; Schider, G.; Leitner, A.; Aussenegg, F. R. (Appl. Phys. Lett., 2003)

(untitled) - Le Ru, E. C.; Etchegoin, P. G. (MRS Bull., 2013)

Proc. Conf. Telecommun. - ConfTele - Ferreira, Q.; Brotas, G.; Alcácer, L.; Morgado, J. (Characterization of self-assembled monolayers of thiols on gold using scanning tunneling microscopy, 2009)
https://www.it.pt/Publications/PaperConference/7432

(untitled) - Minaeva, V. A.; Minaev, B. F.; Hovorun, D. M. (Ukr. Biokhim. Zh., 2008)
http://ubj.biochemistry.org.ua/index.php/en/journal-archive/2008/n-4-july-august-34155/480-vibrational-spectra-of-the-steroid-hormones-estradiol-and-estriol-calculated-by-density-functional-theory-the-role-of-low-frequency-vibrations-minaeva-v-a-minaev-b-f-hovorun-d-m

(untitled) - Vedad, J.; Mojica, E.-R. E.; Desamero, R. Z. B. (Vib. Spectrosc., 2018)